Domestic oratories: an object of memory - Souza, Claudio Rafael Almeida de (2022)
This paper presents the domestic oratories as a space of worship, an object of memory, found in residences in the city of São Salvador da Bahia. It seeks to correlate their esteem as a locus of memory that emerges from the environments where they are located. As a methodology, authors such as Nora (1984), Menezes (1998), Pollak (1989), Halbwachs (1990) Benjamin (2014), Bérgson (1999) and Bosi (1987) were used. The result allows to have knowledge and explanation of the association between the object, the memory and the syncretism of Bahian domestic religiosity. Thus establishing a process of knowledge construction and consequently expanding the information about the configuration of the objects studied per hour.